(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
The article uses CLO3D and HTML5 to design a virtual clothing display system. And for the problems that may arise when using CLO3D to make garments, the solution is given. At the same time, the evaluation of the fit of the virtual clothing made in CLO3D was discussed. Designers can use CLO3D to quickly create virtual clothing in accordance with the users' requirements. After, through the system, designers can publish it on the Web for the users to effectively see the process of cloth making in an all-rounded way, while sustaining communication with designers. The design of this virtual clothing display platform provides some reference value for the digital model of the apparel industry.